Fe-C-Si ternary composite coating on CP-titanium and its tribological properties - Md Abdul, Maleque; Saffina, W.; Ahmad, A.S; Mohammad Yeakub, Ali (Institute of Physics Publishing, 2017)
This study focused on the development of ternary composite coating through incorporation of Fe-C-Si ternary powder mixtures on CP-Ti substrate and characterizes the microstructure, hardness and wears behavior in presence of Jatropha oil. In this work, the surface of commercial purity titanium (CP-Ti) was modified using a tungsten inert gas (TIG) surface melting technique. The wear behavior of coated CP-titanium was performed using pin-on-disk machine. The results showed that the melt track has dendritic microstructure which was homogenously distributed throughout the melt pool. This Fe-C-Si ternary composite coating enhanced the surface hardness of CP-Ti significantly from 175 HV for the untreated substrate to ∼800 HV for the Fe-C-Si coated CP-Ti due to the formation of intermetallic compounds.. The wear results showed that less wear volume loss was observed on the composite coated CP-Ti in presence of Jatropha-biodiesel compared to uncoated CP-Ti. The achievement of this hard Fe-C-Si composite coating on the surface of CP-Ti can broadened new prospect for many engineering applications that use biodiesel under different tribological variables. © Published under licence by IOP Publishing Ltd.